Effects of different gases on foaming properties of protein dispersions prepared with whipped cream dispenser. (February 2022) - Sato, Ai; Matsumiya, Kentaro; Kosugi, Tatsuya; Kubouchi, Hiroaki; Matsumura, Yasuki
Abstract: The whipped cream dispenser is a foaming tool that is an increasingly applied for on-site whipped cream consumption. It creates foams by incorporating nitrous oxide (N2 O) or carbon dioxide (CO2 ) into protein dispersions, while other foaming methods such as agitation and aeration create foam by incorporating air and nitrogen (N2 ). In this study, a whipped cream dispenser was used to investigate the effects of different gases and proteins on the foaming properties of protein dispersions. Four gases (CO2, N2 O, air, N2 ) and five proteins were used. The results show that a higher foaming capacity was obtained for all the protein dispersions that were prepared with more soluble gases (N2 O and CO2 ). The foam that was prepared with the more soluble N2 O was less stable than that prepared with air and N2 . Although the impact of proteins on the foam stability was lower than that of gases, the applying different proteins also significantly changed the foam stability. Highlights: Whipped cream disperser (WCD) was applied to foam food protein dispersions. Impact of gas solubility on foaming properties was larger than protein variety. Highly soluble gas increased the foam capacity of foams prepared by WCD. Highly soluble gas decreased stability of foams prepared by WCD.